Intelligent Computation in Big Data Era : International Conference of Young Computer Scientists, Engineers and Educators, ICYCSEE 2015, Harbin, China, January 10-12, 2015. Proceedings - Wang, Hongzhi; Qi, Haoliang; Che, Wanxiang; Qiu, Zhaowen; Kong, Leilei; Han, Zhongyuan; Lin, Junyu; Lu, Zeguang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the International Conference of Young Computer Scientists, Engineers and Educators, ICYCSEE 2015, held in Harbin, China, in January 2015. The 61 revised full papers presented were carefully reviewed and selected from 200 submissions. The papers cover a wide range of topics related to intelligent computation in Big Data era, such as artificial intelligence, machine learning, algorithms, natural language processing, image processing, MapReduce, social network.
Intelligent computation in Big Data era -- Artificial intelligence -- Machine learning -- Algorithms -- Natural language processing -- Image processing -- MapReduce -- Social network.
Keywords: Data mining; Information storage and retrieva; Artificial intelligence; Computer vision; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Artificial Intelligence; Image Processing and Computer Vision